Humidity sensor based on a multimode-fiber taper coated with polyvinyl alcohol interacting with a fiber bragg grating - Li, Tao (2013)
An optical fiber relative humidity (RH) sensor is proposed and experimentally demonstrated with a multimode-fiber taper coated with a layer of polyvinyl alcohol cascading with a fiber Bragg grating. The operation is based on the interaction between the optical evanescent field and the coating along the taper waist. Humidity changes the refractive index of the extended coating, thus transmission loss of the light signal is introduced and humidity measurement is therefore realized. The measurement sensitivity is enhanced since the light passes through the taper twice. A maximum sensitivity of 1.994 μW/%RH is achieved within the measurement range of 30-95%RH with the taper waist diameter of 50.2 μm. The average response time is ~2 s and the measurement is nearly insensitive to temperature.